Differentiating between viruses and virus species by writing their names correctly - Zerbini, Francisco Murilo (2022)
Funding Information: The authors are members of the International Committee on Taxonomy of Viruses Executive Committee. Funding Information: Research reported in this publication was supported by the National Institute of Allergy and Infectious Diseases of the National Institutes of Health under Award Number U24AI162625 to E.J.L. This work was supported in part through Laulima Government Solutions, LLC prime contract with the US National Institute of Allergy and Infectious Diseases (NIAID) under Contract No. HHSN272201800013C. J.H.K. performed this work as an employee of Tunnell Government Services (TGS), a subcontractor of Laulima Government Solutions, LLC under Contract No. HHSN272201800013C. B.E.D. is supported by the European Research Council (ERC) Consolidator Grant 865694: DiversiPHI, and the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany's Excellence Strategy—EXC 2051—Project-ID 390713860. E.M.A. gratefully acknowledges the support of the Biotechnology and Biological Sciences Research Council (BBSRC); this research was funded by the BBSRC Institute Strategic Program Gut Microbes and Health BB/R012490/1 and its constituent projects BBS/E/F/000PR10353 and BBS/E/F/000PR10356. H.M.O. was supported by University of Helsinki funding for FINStruct and Instruct-ERIC research infrastructure. S.S. acknowledges partial support from the Special Research Initiative (MAFES), Mississippi State University, and from the National Institute of Food and Agriculture, US Department of Agriculture, Hatch Project 1021494. A.R.M. is a Program Director at the U.S. National Science Foundation (NSF); the statements and opinions expressed herein are made in a personal capacity and do not constitute endorsement by NSF or the government of the United States. D.L.R. is supported by the U.K. Medical Research Council (MC_UU_1201412). F.M.Z. is supported by grants from Capes (Finance code 01), CNPq and Fapemig. P.A.Z. is supported by Suzano Papel e Celulose, Capes (Finance code 01), Conselho Nacional de Desenvolvimento Científico e Tecnológico and Fundação de Amparo à Pesquisa do Estado de Minas Gerais. Publisher Copyright: © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature.